Деятельность ЦРУ и МОК по созданию олимпийской команды беженцев - Райдер Тоби К. (National University of Physical Education and Sport of Ukraine, 2016)
The article describes the materials reflecting the efforts of the CIA and the IOC to establish a Refugee Olympic team. Particular attention is paid to the fact that among the millions of refugees there are many athletes of the highest calibre. It is mentioned that in March, 2016 the IOC established and recognized a Refugee Olympic Team.